2019
DOI: 10.1155/2019/2630357
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Prediction of the Active Compounds, Potential Targets, and Signaling Pathways Involved in Danshiliuhao Granule for Treatment of Liver Fibrosis

Abstract: This study aims to predict the active ingredients, potential targets, signaling pathways and investigate the “ingredient-target-pathway” mechanisms involved in the pharmacological action of Danshiliuhao Granule (DSLHG) on liver fibrosis. Pharmacodynamics studies on rats with liver fibrosis showed that DSLHG generated an obvious anti-liver fibrosis action. On this basis, we explored the possible mechanisms underlying its antifibrosis effect using network pharmacology approach. Information about compounds of her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…Silibinin, also known as silybin, serves as the positive control, 25,26 and a number of studies have confirmed its anti-fibrosis effect. [27][28][29] In the medication administration group, byakangelicin (100 mg/ kg) and silibinin (100 mg/kg) were administered after four weeks through oral gavage until the end of eight weeks.…”
Section: Animal Modelmentioning
confidence: 99%
“…Silibinin, also known as silybin, serves as the positive control, 25,26 and a number of studies have confirmed its anti-fibrosis effect. [27][28][29] In the medication administration group, byakangelicin (100 mg/ kg) and silibinin (100 mg/kg) were administered after four weeks through oral gavage until the end of eight weeks.…”
Section: Animal Modelmentioning
confidence: 99%
“…DL represents the ability of potential ingredients to become effective drugs by calculating the similarity with a known drug, which is beneficial to optimize pharmacokinetic properties to affect ADME [17,21]. e active ingredients were considered viable according to ADME features with OB ≥ 30% and DL ≥ 0.18, two critical value that indicate acceptable oral bioavailability and drug-likeness as previously described [22]. All targets (including the validated and predicted targets) related to these active ingredients were extracted from the TCMSP database and entered into the UniProt database [23] (http:// www.uniprot.org/) to obtain target-relevant gene names.…”
Section: Main Active Ingredient Screening and Target Collectionmentioning
confidence: 99%
“…The PCR amplification was performed using genomic DNA as a template. PCR mixture ( [20]. The target prediction for the main active compounds screened out by the above step was performed using the PharmMapper server (http://www.lilabecust.cn/pharmmapper/) with the "Homo sapiens" species setting, and the gene targets of Folium sennae were selected.…”
Section: Pcr Amplification and Sequencingmentioning
confidence: 99%